Benzyl Acetylcarbamate Potassium Salt (BENAC-K): A Simple Nucleophilic N-Acetamide Equivalent - Sakai, Takeo; Tatematsu, Toshiki; Fukuta, Ayumi; Kasai, Satomi; Hayashi, Kahori; Mori, Yuji (Synthesis, 2019)
Benzyl acetylcarbamate potassium salt (BENAC-K) has been developed as a simple nucleophilic acetamide equivalent. A broad variety of alkyl halides were converted into benzyloxycarbonyl-protected N-alkylacetamides in high yields by simple treatment with an almost equimolar (1.1 equiv) amount of BENAC-K in a polar solvent.
Keywords: alkylation; acetamide; SN2 reaction; nitrogen nucleophile; BENAC-K